Cover Picture: Metal Dendrimers: Synthesis of Hierarchically Stellated Nanocrystals by Sequential Seed‐Directed Overgrowth (Angew. Chem. Int. Ed. 4/2015). Issue 4 (17th December 2014) - Weiner, Rebecca G.; Skrabalak, Sara E.
<x xml:space="preserve">Abstract</x> Nature seeds pathways to hierarchical structures, which scientists strive to emulate through the synthesis of advanced nanostructures. In their Communication on page 1181 ff., R. G. Weiner and S. E. Skrabalak describe the synthesis of hierarchically stellated nanocrystals by sequential seed‐directed overgrowth. These structures are analogous to organic dendrimers, but seed symmetry, rather than molecular connectivity, directs the multi‐level branching (Image designed by Ella Marushchenko, Scientific Illustrations).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>